Trajectories of aggressive and depressive symptoms in male and female overweight children: Do they share a common path or do they follow different routes? - Almenara Vargas, Carlos Arturo (2017)
Proyecto de investigación 2017-2019, financiado por la Universidad Peruana de Ciencias Aplicadas (UPC).